Fungal fairy rings: history, ecology, dynamics and engineering functions - Maurizio Zotti; Giuliano Bonanomi; Stefano Mazzoleni (IMA Fungus)
Fungal fairy rings (FFR) are fascinating natural phenomena that have intrigued people and scientists for centuries. These patterns, often represented by circular distributions of altered vegetation, are found in grasslands and forest habitats. Fairy rings occur when fungi grow radially in the soil, raising from a central point, progressively degrading organic matter and thus affecting vegetation. The observation of such spatial patterns allows mycologists to conduct an in-depth analysis of the role of fungi in ecosystems. This review presents the current knowledge and scientific advancement of the studies of FFRs. An historical appraisal from the most representative pioneer studies until recent works is presented in different scientific fields, including microbiology, chemistry, botany and ecology. Based on a deep analysis of bibliographic data, we synopsised different aspects of FFRs: i) history of studies, ii) taxonomy, iii) ecology (environmental conditions and biogeography), iv) classification of vegetation patterns, v) spatial dynamics, vi) role as ecosystem engineer (impact on soil chemistry, plants and microbiota). In conclusion, beside still open research areas requiring further investigation, a schematic functional model of fungal fairy rings is proposed, in which on one hand the dynamics of the fungal mycelium is explained by self-DNA accumulation and the build-up of autotoxicity. On the other hand, the effects of fungi on plants are related to the intermingled and differently spatially distributed effects of hydrophobicity, phytotoxicity and phytostimulation.